Membangun Loyalitas Karyawan di Lembaga Budaya: Peran Motivasi, Budaya Organisasi, dan Pelatihan di UPTD. Monumen Perjuangan Rakyat Bali - Ni Putu Ayu Rishya Maharani; I Gst. Ayu Wirati Adriati; Nyoman Sri Manik Parasari; Putu Dyah Permatha Korry (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Differences in treatment between civil servants and contract employees continue to influence work dynamics within public institutions. At the Bali Struggle Monument (MPRB), disparities in employment status, training opportunities, and reward mechanisms have the potential to reduce employees’ sense of fairness and loyalty. This study aims to examine the influence of motivation, organizational culture, and training both individually and simultaneously on employee loyalty. The sample in this research consisted of 82 employees at UPTD Monumen Perjuangan Rakyat Bali. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, the coefficient of determination, as well as F-tests and t-tests. The findings show that motivation has a positive and significant effect on employee loyalty, organizational culture also has a positive and significant effect, and training likewise demonstrates a positive and significant impact on loyalty. In addition, motivation, organizational culture, and training together significantly influence employee loyalty.